Average of trial peaks versus peak of average profile: impact on change of direction biomechanics - Dallas, G.; Theodorou, A. S. (Sports Biomechanics, 2020)
The aims of this study were twofold: firstly, to compare lower limb kinematic and kinetic variables during a sprint and 90° cutting task between two averaging methods of obtaining discrete data (peak of average profile vs. average of individual trial peaks); secondly, to determine the effect of averaging methods on participant ranking of each variable within a group. Twenty-two participants, from multiple sports, performed a 90° cut, whereby lower limb kinematics and kinetics were assessed via 3D motion and ground reaction force (GRF) analysis. Six of the eight dependent variables (vertical and horizontal GRF; hip flexor, knee flexor, and knee abduction moments, and knee abduction angle) were significantly greater (p <= 0.001, g <= 0.10-0.37, 2.74-10.40%) when expressed as an average of trial peaks compared to peak of average profiles. Trivial (g <= 0.04) and minimal differences (<= 0.94%) were observed in peak hip and knee flexion angle between averaging methods. Very strong correlations (p >= 0.901, p < 0.001) were observed for rankings of participants between averaging methods for all variables. Practitioners and researchers should obtain discrete data based on the average of trial peaks because it is not influenced by misalignments and variations in trial peak locations, in contrast to the peak from average profile.